Speaking Through Silence: Wittgenstein on the Unsayable (NBPA Journal for Arts, Humanities & Social Sciences, 2025)
The book Tractatus Logico-Philosophicus (henceforth TLP), written by L. Wittgenstein, is a work consisting of seven propositions. Among them, the last enigmatic proposition is on the concept of silence, which says that what we are unable to talk about must remain silent. This statement has provoked intense debate over its meaning, implications, and place within the broader trajectory of his philosophy. This article explores Wittgenstein’s concept of silence as more than a negation of speech; rather, it functions as a boundary marker that reveals the limits of language and gestures toward dimensions of experience that cannot be captured discursively. By situating silence within the logical structure of the Tractatus, the study highlights how Wittgenstein delineates the sayable—the world of facts, logic, and science—from the unsayable—the ethical, the aesthetic, and the mystical. The paper examines how silence speaks by drawing attention to what resists expression yet remains vital to human life. Special attention is given to interpretive debates: the ‘traditional’ view, which regards Wittgenstein as affirming ineffable truths, and the ‘resolute’ reading, which sees his silence as a therapeutic rejection of metaphysical speculation. Ultimately, the paper argues that Wittgenstein’s silence is not an endpoint of thought but an invitation to reorient philosophy’s task: to clarify language, dissolve confusions, and recognise the significance of what lies beyond propositional discourse. In this way, Wittgenstein ‘speaks through silence,’ not by offering ineffable doctrines, but by showing that the most profound aspects of existence are revealed precisely at the point where words fail.